(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: A comprehensive assessment of the physical growth of preterm infants receiving early enteral nutrition at the Pediatrics Department of Thai Nguyen Central Hospital, 2023- 2024. Research objects and methods: A cross-sectional descriptive research was carried out involving 204 preterm infants who were given early enteral nutrition. Results: This study found that the male-to-female ratio among preterm infants was 1.8/1, with cesarean section deliveries accounting for the highest proportion at 70.6%. The group with birth weights between 1500-2499g had the longest time to regain their birth weight, with 72.1% of infants recovering within 10-14 days, while infants weighing ≥2500g regained their birth weight in less than 10 days. The catch-up growth rate at week 3 (T3) was 67,6%, and at week 4 (T4), it was 70,9%. Conclusion: Early gastrointestinal feeding in preterm infants at the Pediatrics Department of Thai Nguyen Central Hospital is a safe and effective approach with minimal complications, promoting rapid recovery of birth weight.